Sekolah Etnis Tionghoa Di Jakarta Pada Masa Pemerintahan Presiden Soeharto (1966-1998) - Dwi Sudibyo; Sumaryoto Sumaryoto; Sumaryati Sumaryati (Herodotus: Jurnal Pendidikan IPS, 2025)
The purpose of the study was to find out the social, economic and educational conditions of the Chinese community in the early days of President Soeharto's administration; to find out the policies of President Soeharto's administration towards the Chinese ethnic group in Jakarta in the field of education; to find out the development of Chinese ethnic schools in Jakarta during the late days of President Soeharto's administration in Jakarta; Based on the results of the study: 1) That after the 1950s, the government of the Republic of Indonesia tried to build Indonesia's economic life. One way is to develop indigenous entrepreneurs; 2) That Chinese politics during the New Order era was a "Broker" type of politics, the interests of the Chinese people were represented by several Chinese figures who had relations with the authorities; 3) That after the New Order government collapsed, education for Chinese children in Indonesia was freer. During the period of approximately 32 years of the New Order era, there were no books in Mandarin. However, the situation changed after the New Order government led by President Soeharto collapsed on May 21, 1998.